ESP Students’ Perception on Role Playing for Boosting Their Speaking Skill - Zulfa, Puspa Fortuna; Suryanti, Ery; Tazali, Imam (English Education and Literature Journal (E-Jou), 2024)
English for Specific Purposes (ESP) emphasizes on the use of English related to the students’ major taken. It is manifested in four skills and one of them is speaking skill. The role-playing learning technique has been implemented for boosting their speaking skill. The aim of this research is to find students’ perception towards the application of the role-playing learning technique in boosting students' speaking skill. As much as 31 students of Information System and Accounting Information System majors were employed to this research and it was conducted in Universitas Bina Sarana Informatika. This research was a descriptive and analyzed qualitatively. The data were gathered from students’ perception which were obtained from their fulfillment of online form and also an open-ended interview. There were 13 questions to investigate and dig students’ perception and it has represented the data. It resulted that they had positive perception towards the implementation of role-playing in English class with details: good for boosting linguistics (1). Accuracy of speech, 2). Appropriate placement of pressure, tone, joints and duration. 3). Word choice (diction). and 4). Accuracy of conversational targets (use of sentences)) and non-linguistics skills (natural, calm and not stiff, as well as their self-confidence). In conclusion, role playing can be recommendation for learning speaking English, not only for students in primary education, but also students in higher education.